2010
DOI: 10.1016/j.jelechem.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of chronopotentiometric transients of ion-selective membranes with two transition times

Abstract: Passing currents through ion-selective membranes has contributed to the development of a variety of novel methods. In this work, chronopotentiometric (CP) transients with two transition times (breakpoints) are presented for the first time, with the theoretical interpretation of such voltage transients. The validity of our theory has been confirmed in experiments utilizing ETH 5294 chromoionophore-based pH sensitive membranes with and without lipophilic background electrolyte and ETH 5234 ionophore-based calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…This behavior may be attributed to the transport of anions with different size, molar concentrations, mobility or diffusion coefficients in the membrane matrix. A similar characteristic was observed by Zook et al (135). The authors studied the ion transport through a Ca 2+ selective membrane in contact with a solution containing an ionophore and calcium cations.…”
Section: Equation 32supporting
confidence: 74%
“…This behavior may be attributed to the transport of anions with different size, molar concentrations, mobility or diffusion coefficients in the membrane matrix. A similar characteristic was observed by Zook et al (135). The authors studied the ion transport through a Ca 2+ selective membrane in contact with a solution containing an ionophore and calcium cations.…”
Section: Equation 32supporting
confidence: 74%
“…The occurrence of several transition times in the chronopotentiograms of multicomponent solutions has also been observed by several authors. In this way, Zook et al [45], who evaluated the transport through a calcium-selective membrane submerged in a solution containing ionophore and calcium cations, found two inflection points in the chonopotentiometric curves: the first one attributed to the transport of free ionophore, and the second one assigned to the ion-ionophore complex transfer. Both inflexion points were completely separated, as a result of the difference in ion mobility and diffusion coefficient.…”
Section: 𝜅 𝐹 𝑧 𝑢 𝐶mentioning
confidence: 99%
“…[36]. The authors studied the ion transport through a Ca 2+ selective membrane in contact with a solution containing an ionophore and calcium cations.…”
Section: Effect Of the Formation Of Anionic Chelatesmentioning
confidence: 99%
“…The authors studied the ion transport through a Ca 2+ selective membrane in contact with a solution containing an ionophore and calcium cations. According to the authors, the first inflexion point was assigned to the transport of free ionophore, the second inflexion point was attributed to ion-ionophore complex transfer and both inflexion points were clearly separated from each other, indicating a difference in ion mobility and diffusion coefficient [36]. Pismenskaya et al [37] reported that pH changes on a membrane surface due to the preferential transport of hydroxyl ions may also modify the transport properties of weak electrolyte anions, depending on the membrane selectivity for each charged species.…”
Section: Effect Of the Formation Of Anionic Chelatesmentioning
confidence: 99%